Novel Antennapedia and Ultrabithorax trimeric complexes with TBP and Exd regulate transcription - Villarreal Puente, Alely Cecilia; Altamirano Torres, Claudia Dalila; Jiménez Mejía, Gustavo; Hernández Bautista, Norma Carolina; Montalvo Méndez, Rubén de Jesús; Vázquez, Martha; Zurita, Mario; Reséndez Pérez, Diana (2024)
Background Hox proteins interact with DNA and many other proteins, co-factors, transcriptional factors, chromatin remodeling components, non-coding RNAs and even the extracellular matrix that assembles the Hox complexes. The number of interacting partners continues to grow with diverse components and more transcriptional factors than initially thought. Hox complexes present many activities, but their molecular mechanisms to modulate their target genes remain unsolved.